Risco como dispositivo biopolítico e seus sentidos frente ao novo coronavírus: cartografia da pandemia de covid-19 no Brasil - Nascimento, Ana Maria Guedes do (2022)
This thesis discusses the production of risk discourse, pointing out how intervention models and health care can collaborate to control life, beyond epidemiological and health issues. In such a way, it seeks to understand how risk speeches have been produced and disseminated facing the new coronavirus, and also how this discourse triggers mechanisms of power. Considering the context of the pandemic, which the world has been going through since the end of 2019 and the wide dissemination of the probabilities of illness and death by COVID-19, a mapping of the information released by competent bodies was carried out, as being effective measures, to control the pandemic, understanding that this information contributes to the construction of a narrative about the risks facing the vírus. The cartographic method was chosen for investigation, which took place by collecting and analyzing the statements of decrees, laws, norms and various recommendations, carried out with the interest of controlling the spread of the virus, as well of caring for those who were sick. Some news were also collected from the press, from the speeches and postures of the heads of government, especially from the President of the Republic, where, since the beginning of the health crisis, there was a discrepancy between what was prescribed, what was said and what was practiced. Concepts such as biopower, biopolitics and necropolitics were triggered, in order to verify the power games involved in the legitimation of narratives and production of truths, so that the risky discourse could be thought of as a power device. We can follow how the narrative about the risk of getting sick and dying from covid-19, produced by the dome of the federal executive power, was being appropriated and resignified for government purposes. This strategic set of information that clashes with the scientific knowledge produced about the pandemic can be defined as a discourse of disinformation, whose political action aims to erase measures to protect life in favor of the neoliberal economy. This discourse was seized, defended and disseminated by supporters of bolsonarism, so that it gave new understandings about the virus and the pandemic, capable of changing the perception of part of the population in relation to the dimension of the problem faced. In this way, the risk was being conducted as a biopolitical dispositive, where, as pain, suffering and death were minimized, the idea of risk of poverty, hunger and unemployment was reinforced by the population's adherence to tools to contain the spread of the disease.